Pengaruh Kualitas Pelayanan Sistem Inapornet Terhadap Kepuasan Pengguna Jasa - Agus Setiono, Beni; Melinda, Nova (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2022)
The purpose of this research is to examine and analyze the Influence of Inapornet System Service Quality on Service User Satisfaction at PT. Delta Artha Bahari Nusantara Probolinggo Branch, where the Inaportnet System is an operating system and integration of service activities and licensing (clearance) from related agencies that carry out activities at the port. The research approach uses a quantitative approach, analyzing data with statistics with the aim of testing hypotheses. The population in this study are users of ship and goods services at PT. Delta Artha Bahari Nusantara Probolinggo Branch with a sample of 30 people. Data analysis with Simple Linear Regression Analysis. From the results of hypothesis testing it is known that the Inaportnet system service has a positive and significant influence on service user satisfaction at PT. Delta Artha Bahari Nusantara Probolinggo Branch.